CALCULATION OF OPTIMAL INTERVALS TO CHOOSE THE MODES OF INTERACTION BETWEEN STATIONS AND NON-PUBLIC TRACKS - Elovoy, I. A.; Potylkin, Y. N. (Science and Transport Progress, 2016)
Purpose. The article is aimed to obtain the operational dependences for calculating the optimal intervals between car supply on loading and unloading fronts, unloading according to the criterion of minimizing operating costs. This will allow substantiating the choice of effective modes of interaction between railway stations and non-public tracks. Methodology. Methods of scientific analysis and synthesis, the method of Brandon at the approximation of the function, experimental and statistical methods of compiling the mathematical dependences were used in order to achieve the purpose. Findings. There were obtained the formulas for determination of: 1) optimal values of intervals between the car supplies to the places of loading and unloading according to the criterion of cost minimization in conditions of interaction between railway stations and non-public tracks through determined time periods; 2) medium-sized car groups in one supply on the non-public track, 3) the duration of the shunting work on car spotting in loading and unloading fronts. Originality. Operational dependences were improved for the determination of optimal values of intervals between the car supplies to the fronts of loading, unloading according to the criterion of minimizing the operational costs. Since the obtained formulas take into account the influence of: 1) the number of freight fronts involved in shunting operations with the cars near the points of loading and unloading; 2) the average number and size of the car groups, which are on the non-public tracks; 3) average size of the car supply-removal; 4) the presence of the goods siding for the fronts recharging; 5) total length of the tracks involved in recharging of the loading and unloading fronts. Practical value. The obtained operational dependences can be used in determining the parameters of supply-removal cycle to the loading and unloading fronts, the optimal values of the intervals between supplies in the interaction between the railway station and non-public tracks. Obtained results will allow: 1) identifying weak positions in the organization of connecting station operation and non-public tracks; 2) reducing the costs of the owners of non-public tracks and the general railway by minimizing the economic and time losses and, as a consequence, increasing the competitiveness of railway transport in the transport market.